Toyir EXPERIMENTAL DETERMINATION OF THE CLEANING EFFICIENCY OF THE FIBER IN THE PIPE: Experimental studies are presented in the article in order to improve the efficiency of fiber cleaning in the pipe in textile enterprises. - Diyorov, Husan (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Cleaning the fiber from impurities in textile enterprises consists in increasing the cleaning efficiency of the fiber due to the installation of a special pipe in the front part of the cleaning machine.